Artificial Intelligence Impact on Elements of National Power: Implications on Pakistan’s National Security - Zohaib Altaf; Nimra Javed, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
Artificial Intelligence (AI) has assumed a pivotal role as a determinant of national power, with a specific focus on its ramifications on military prowess, demographic dynamics, and economic affluence. This investigation adopts the lens of the Social Construction of AI theory, which accentuates the sociocultural shaping of AI, employing a qualitative research methodology to comprehensively grasp the multifaceted impacts of AI on these three dimensions of national power. The study uses both the primary and secondary sources to analyse the role of AI in national power. It posits that the influence of AI is inherently disparate across states, contingent upon a complex interplay of political, economic, and contextual factors. Within the military realm, states are channeling substantial resources into the development of advanced weaponry. In economic domain, the impact of AI-induced transformations on wealth accumulation is more significant in the developed nations than in the developing ones. Similarly, the effect of AI on the population of nation and its power can vary based on the unique domestic factors in each country. This study contends that the trajectory of AI advancement engenders multifarious implications for Pakistan's national security landscape.